Insanity, identity and empire : immigrants and institutional confinement in Australia and New Zealand, 1873-1910 - Coleborne, Catharine (Studes in imperialism., 2015)
Based on over 3000 institutional records, Coleborne's study will have wider relevance outside of the history of medicine and psychiatry. It has a global perspective but focuses on specific destinations, and in so doing, contributes in an innovative way to global history and the history of human migration.